Pancreatic hemangioma manifesting as variceal gastroesophageal bleeding during pregnancy: case report - Franzoni, Leticia de Campos [UNESP]; Villar, Clarissa Ribeiro [UNESP]; Carraretto, Fernanda Plazzi [UNESP]; Yamashiro, Fabio da Silva [UNESP]; Oliveira, Cassio Vieira de [UNESP]; Sassaki, Ligia Yukie [UNESP]; Romeiro, Fernando Gomes [UNESP] (My University, 2012)
There are only 10 reported cases of pancreatic hemangiomas in adults, only one of them causing digestive bleeding. We present a case of variceal bleeding and portal hypertension caused by a pancreatic hemangioma. The patient had 19 year-old and was received at her 16th week of pregnancy. She had massive hematemesis, controlled after variceal band ligation. Her image exams revealed a cystic lesion of 164 cm³ in the pancreas tail and signs of portal hypertension. Two months after, the ultrassonographic exam documented the lesion growth, achieving 200 cm³ at that time. The patient was submitted to distal pancreatectomy, and the histopathological analysis revealed a pancreatic hemangioma of 11 x 9 x 8 cm. Therefore, we report the second case of digestive bleeding caused by a pancreatic hemangioma, which had a well documented growth during the pregnancy. Additionally, we review the previous reports of pancreatic hemangiomas and discuss the hypothesis of hormonal infl uence on the natural history of these tumors.

Os pseudotumores infl amatórios são um conjunto de lesões raras, caracterizadas histologicamente por proliferação de fi broblastos e células infl amatórias permeadas por estroma fi broso. Nos casos de localização hepática, estas massas são difíceis de diferenciar de outras lesões, especialmente de neoplasias primárias ou secundárias. Descrevemos um caso em que os achados clínicos- laboratoriais e as imagens da ultrassonografi a e da tomografi a computadorizada de abdomen não foram sufi cientes para afastar uma neoplasia, e só foi possível estabelecer o diagnóstico através da biópsia direta, mediante ressecção cirúrgica da lesão. Diante de um paciente sem antecedentes dignos de nota, com massa hepática e marcadores tumorais negativos, o pseudotumor infl amatório de fígado deve ser lembrado sempre como um possível diagnóstico diferencial.
Hemangioma pancreático, manifestando com hemorragia digestiva alta varicosa durante gestação: relato de caso
Keywords: Pancreatic hemangioma; Portal hypertension; Esophageal varices; Gestation; Hemangioma pancreático; Hipertensão portal; Varizes esofágicas; Gestação